Mismatch Cleavage Detects Base Deletion in Cystic Fibrosis Gene. (October 1998) - Hsu, Ih-Chang; Highsmith, W. Edward; Xu, Jingfan; Kong, Dehe
The ΔF508 is the most common defect in the cystic fibrosis (CF) gene; it involves in a 3-base deletion in codon 508 and results in the loss of a phenylalanine residue at amino acid position 508. Our previous results have shown the mismatch enzyme cleavage at the mismatch of a DNA duplex in identifying a specific DNA sequence or a point mutation. The assay is simple and reliable. By manipulating the melting temperature (Tm) for the hybrids of the DNA targets and the deoxynucleotide probes, the mismatch cleavage assays are able to detect the most common defective CF gene, ΔF508. The assays with a ΔF508 and a normal wild-type probe can differentiate the three genotypes, i.e., ΔF508/ΔF508, ΔF508/normal and normal/normal. Furthermore, the addition of ammonium acetate amplifier to the assay for recycling the target DNA can increase the sensitivity to a level that is sufficient to detect the mutated target in a few micrograms of genomic DNA without the aid of PCR amplification. The detection of the base deletion, the amplification of sensitivity and the differentiation among the genotypes of normal, carrier ΔF508 and mutant ΔF508 suggest the useful application of mismatch cleavage in genetic diagnosis at the DNA level.